Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.25255/jbm.2019.7.3.252.263
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors that affect E-government Implementation in Jordan over Time

Abstract: The Information and Communication Technology (ICT), especially the Internet, revolution has dramatically changed how citizens can interact with their government. E-government, that is utilising ICT to change and/or improve the relationship between government, citizens, businesses and other government entities (World Bank 2007), has become a popular focus of government efforts in many developed and developing countries. Jordan is one such developing country that has embarked on an e-government initiative. Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…G2C and G2E represent the interaction between government and individuals, whilst G2B and G2G represent the interaction between government and organizations. Kanaan, Hussein, & Abumatar (2019a) makes a similar conclusion in his research.…”
Section: Review Of Related Literaturesupporting
confidence: 73%
“…G2C and G2E represent the interaction between government and individuals, whilst G2B and G2G represent the interaction between government and organizations. Kanaan, Hussein, & Abumatar (2019a) makes a similar conclusion in his research.…”
Section: Review Of Related Literaturesupporting
confidence: 73%
“…In a qualitative-based study, Alomari et al (2014) found wasta was one of the main social and cultural factors that would lead Jordanian people to question the use of e-government services. Kanaan et al (2019) conducted a qualitative-based study on the implementation of e-government which found wasta to be one of the main cultural factors that would affect the success of e-government implementation in Jordan.…”
Section: Review Of the Literaturementioning
confidence: 99%